2017
DOI: 10.1111/epi.13932
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical functional connectivity in Lennox–Gastaut syndrome is abnormally enhanced in executive‐control and default‐mode networks

Abstract: Specific thalamocortical circuits are affected in LGS. Functional connectivity is abnormally enhanced between the mediodorsal and ventrolateral thalamus and the default-mode and executive-control networks, thalamocortical circuits that normally support diverse cognitive processes. In contrast, thalamic regions connecting with primary and sensory cortical networks appear to be less affected. Our previous neuroimaging studies show that epileptic activity in LGS is expressed via the default-mode and executive-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
(157 reference statements)
1
24
2
Order By: Relevance
“…Furthermore, understanding the CM’s functional connectivity may assist with presurgical planning. For example, observation of a connectivity pattern consistent with the one we report here may increase confidence in the accuracy of the planned electrode placement within the CM, whereas observation of a dissimilar pattern—as occurs when connectivity is calculated from a different thalamic nucleus in patients with LGS31—may suggest potential misplacement.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, understanding the CM’s functional connectivity may assist with presurgical planning. For example, observation of a connectivity pattern consistent with the one we report here may increase confidence in the accuracy of the planned electrode placement within the CM, whereas observation of a dissimilar pattern—as occurs when connectivity is calculated from a different thalamic nucleus in patients with LGS31—may suggest potential misplacement.…”
Section: Discussionsupporting
confidence: 68%
“…A study using 3T proton density-weighted MRI also reported delineation of the CM in controls29; however, the need for coarse slice thickness (~3 mm) to achieve sufficient signal-to-noise ratio may limit the method’s neurosurgical suitability. Functional approaches for localising CM, such as task-based fMRI paradigms that activate CM specifically30 or thalamic segmentations based on resting-state fMRI connectivity,31 may assist with refining the visualisation achievable by structural MRI; however, further clinical validation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Several research‐only studies of specific epilepsies have also been undertaken at our center with targeted recruitment—these do not form any part of this cohort and are described elsewhere (childhood absence epilepsy; Lennox‐Gastaut syndrome; benign epilepsy with centrotemporal spikes).…”
Section: Methodsmentioning
confidence: 99%
“…Full details of the EEG‐fMRI protocol have been described previously (GE Signa Siemens Trio; Siemens Skyra). In brief, fMRI data were obtained using a gradient‐recalled echo planar imaging with blood oxygenation–level dependent (BOLD) weighting and whole‐brain slice coverage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation